Menjadi Pendidik Anak Usia Dini Yang Profesional - Alfi, Alfiyatul Hasanah (Program Studi Pendidikan Islam Anak Usia Dini, 2023)
The number of early childhood education institutions in Indonesia is growing rapidly. This increase occurred in line with the large number of early childhood children (AUD) that must be served. The quantity is directly proportional to the need for qualified teachers. The demand for the quality of educators is increasingly clear by returning early childhood development which is a golden period so that a good foundation from quality teachers has an impact on the excellence of the Indonesian generation. For this reason, it is necessary for PAUD educators to understand these maximizing opportunities from an early age. There needs to be an effort to improve the quality of education services for early childhood by improving the quality of early childhood educators. Professionalism itself has not been understood by PAUD because it is not limited to intention or desire. His sincerity must be reflected in action. PAUD teacher certification provides a positive meaning so that PAUD teachers remain consistent in improving their own professionalism. PGPAUD needs introspection to try all ways to increase the competitiveness of graduates as well as academic products and other services, which among other things is achieved through improving the quality of education so that it has quality excellence. Keywords: PAUD, Professionalism, teacher